1999
DOI: 10.1103/physreve.59.6361
|View full text |Cite
|
Sign up to set email alerts
|

Theory of theNO+COsurface-reaction model

Abstract: We derive a pair approximation (PA) for the NO+CO model with instantaneous reactions. For both the triangular and square lattices, the PA, derived here using a simpler approach, yields a phase diagram with an active state for CO-fractions y in the interval y 1 < y < y 2 , with a continuous (discontinuous) phase transition to a poisoned state at y 1 (y 2 ). This is in qualitative agreement with simulation for the triangular lattice, where our theory gives a rather accurate prediction for y 2 . To obtain the cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Using Monte Carlo simulations they found that this surface model presents the main features of the pure CO-O 2 system, which contains an active phase where the carbon dioxide molecules are produced continuously. After the appearance of this article, an avalanche of other papers concerning the reaction catalytic surfaces also have appeared in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. In general, these papers are related with the own ZGB model or they are extensions of the same, concerning the various aspects of the experimental observations of these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Using Monte Carlo simulations they found that this surface model presents the main features of the pure CO-O 2 system, which contains an active phase where the carbon dioxide molecules are produced continuously. After the appearance of this article, an avalanche of other papers concerning the reaction catalytic surfaces also have appeared in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. In general, these papers are related with the own ZGB model or they are extensions of the same, concerning the various aspects of the experimental observations of these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the transition probabilities we proceed in a manner similar to that used in the site mean-field approximation, but now they are more involved. Examples of the application of this pair approximation can be found in the references [34] and [35]. In particular, in the appendix B of the reference [34], a detailed description of the method used here is given, with emphasis to the N O + CO reaction model.…”
Section: B Pair Approximationmentioning
confidence: 99%
“…Examples of the application of this pair approximation can be found in the references [34] and [35]. In particular, in the appendix B of the reference [34], a detailed description of the method used here is given, with emphasis to the N O + CO reaction model. The reaction probability Π AA was defined as being the probability of an arriving A monomer to react with anyone of its nearest neighbor A on the lattice, in the presence of the B monomers.…”
Section: B Pair Approximationmentioning
confidence: 99%
“…On the other hand, very recently an elaborated mean-field theory of the YK model has been developed up to the pair-approximation level [138] that yields a very accurate estimation of the coexistence point, namely P 2CO = 0.363.…”
Section: The Catalytic Reaction Between Nitrogen Monoxide and Carbon mentioning
confidence: 99%
“…The reactions given by equations (31) and (32) are assumed to be instantaneous (infinity reaction rate limit) while the limiting steps are the adsorption events given by equations (29) and (30 [134,135,136,137,138,139].…”
Section: The Catalytic Reaction Between Nitrogen Monoxide and Carbon mentioning
confidence: 99%